Sintering Temperature and Deposition Orientation Effects on Mechanical, Physical Properties and Geometric Distortion of Cu–Ni Single and Multi Material Indirect Sintering Products (Makara Journal of Science, 2012)
Development of multi material mechanical parts is constantly undertaken to increase functional aspectsas well as life cycle. One example is the use of bimaterial which is widely used as a temperature contactor. This paper presents mechanical, physical properties and geometric distortion of Cu-Ni indirect sintering products used to develop Cu-Ni bimaterial products. The experiment was executed with the following method: firstly, Cu and/or Ni powders were deposited into cast iron powder as the supporting powder. Secondly, it was heated in a furnace with varying temperatures of 870 C, 900 C and 930 C with a holding time of four hours. Lastly, deposition orientation was varied to observe the effect on the occurence of shrinkage. To initiate the multi materials sintering process, single material sintering was performed to observe the physical and mechanical properties. Based on previous work, multi material sintering of Cu and Ni powders was conducted. The experiment results showed that the geometric distortion of the sintering products was influenced by deposition orientation. The Cu and Ni products shrinkage were 49% and 35.33%, respectively. Although the melting temperature of Cu and Ni is close, the binding mechanism of the sintered product did not occur. The significant difference of shrinkage levels was the main factor for the binding mechanism failure between Cu and Ni materials.